2006
DOI: 10.1111/j.0014-3820.2006.tb01082.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fitness Effects of Outcrossing in Calylophus Serrulatus, a Permanent Translocation Heterozygote

Abstract: Small and relatively isolated populations that occupy fragmented habitat are at risk of local extinction. However, fitness consequences of fragmentation related to mating distance, such as inbreeding depression following increased self- and near-neighbor mating, may not follow standard expectations in species with specialized genetic systems. We investigated the effect of mating distance on progeny fitness in Calylophus serrulatus, a primarily autogamous, permanent translocation heterozygote that is restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 101 publications
0
11
1
Order By: Relevance
“…I may have detected optimal outcrossing distance in the form of greater fitness of intrahabitat progeny had I sampled more geographically separated populations. Other studies have detected optimal outcrossing distances (Edmands 2002; but see Peer and Taborsky 2005;Heiser and Shaw 2006), though not always at spatial scales greater than the 17-162-km scale of this study. For example, Fenster and Galloway (2000) did not detect optimal outcrossing at distances greater than 2000 km.…”
Section: Discussioncontrasting
confidence: 44%
“…I may have detected optimal outcrossing distance in the form of greater fitness of intrahabitat progeny had I sampled more geographically separated populations. Other studies have detected optimal outcrossing distances (Edmands 2002; but see Peer and Taborsky 2005;Heiser and Shaw 2006), though not always at spatial scales greater than the 17-162-km scale of this study. For example, Fenster and Galloway (2000) did not detect optimal outcrossing at distances greater than 2000 km.…”
Section: Discussioncontrasting
confidence: 44%
“…However, given the lack of migrants to these populations due to the intensive agriculture of the surrounding landscape (Madson, 1990), species in this type of situation may be considered as candidates for artificial migration as a management approach for longterm success, as has been done in other species (Lande, 1999). Given the potential negative consequences of outbreeding depression from break-up of co-adapted gene complexes (favourable epistatic interactions are known to exist in this species, Fenster & Galloway, 2000a, b;but see Erickson & Fenster, 2006), both careful choice of source for the migrants as well as assessment of hybrids would be prudent as outbreeding depression has been documented at a small scale for other prairie species (Heiser & Shaw, 2006;Wagenius et al, 2010). Management of the species in highly fragmented sites will need a balance between limiting genetic drift load as evident in this species and the potential of outbreeding depression.…”
Section: Application To Conservation Of Prairiesmentioning
confidence: 99%
“…Concordant with the finding that inbreeding tends to reduce individual fitness and the expectation that members of a single small population may be closely related, some studies have demonstrated heterosis, with fitness of progeny from interpopulation mating exceeding that of progeny from random mating within populations (e.g., Richards 2000;Ebert et al 2002;Luijten et al 2002;Paland and Schmid 2003). Other studies, however, have documented outbreeding depression, that is, reduction in seed production or offspring fitness with crossing at various distances, even down to 10 m (e.g., Waser and Price 1994;Edmands 1999;Montalvo and Ellstrand 2001;Quilichini et al 2001;Heiser and Shaw 2006).…”
mentioning
confidence: 99%